2005
DOI: 10.1007/s11172-005-0420-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast determination of reaction kinetic parameters with the use of microwave heating. Kinetics of decomposition of organic substances with nitric acid

Abstract: A mathematical model for the kinetics of a chemical reaction under microwave irradiation in a close volume in the simplest approximation of the uniform temperature and pressure distribution in a system was proposed. The previously proposed dynamic method for determi nation of the activation energy of oxidation of organic substances with nitric acid was substan tiated. According to this method, the activation energy is determined from the experimental exponential plot for the pressure in the nonisothermic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For instance, nitric acid was used to study the kinetics of the decomposition of organic substances under microwave irradiation. One can assume that the reaction implying nitrate and isopropanol must be involved in the exothermic phenomenon observed. To confirm this hypothesis, we first recovered the remaining filtrate after microwave-assisted synthesis for analysis using a coupled gas chromatography/mass spectrometry performed by the CNRS Central Service of Analysis (SCA Vernaison).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, nitric acid was used to study the kinetics of the decomposition of organic substances under microwave irradiation. One can assume that the reaction implying nitrate and isopropanol must be involved in the exothermic phenomenon observed. To confirm this hypothesis, we first recovered the remaining filtrate after microwave-assisted synthesis for analysis using a coupled gas chromatography/mass spectrometry performed by the CNRS Central Service of Analysis (SCA Vernaison).…”
Section: Resultsmentioning
confidence: 99%
“…The strong increase of the internal pressure is indicative of a decomposition reaction. It has already been reported that microwave irradiation is able to induce side reactions: decomposition of organics molecules, [10] redox processes [5] and decomposition of ionic liquids. [11] The reaction mixture also contained some diethyl ether molecules as solvent, which are considered as inert under microwave irradiation since they are non-polar.…”
mentioning
confidence: 99%
“…The experiments were performed with the suspensions of class 2-4 pellets, weighing 10 g and containing 21.4% of soda, in the heating regime from 500 to 800 • C, based on the differential method [34,35] and dynamic method [36] applied for nonisothermal processes. The heating duration was 20 min and the average heating rate was 15 • C/min.…”
Section: Kinetic Studies Of the Wolframite Concentrate Sintering With...mentioning
confidence: 99%